FAKTOR-FAKTOR YANG MEMPENGARUHI GANGGUAN PENDENGARAN PADA PEKERJA PABRIK KELAPA SAWIT PT DELIMA MAKMUR KECAMATAN SINGKIL UTARA KABUPATEN ACEH SINGKIL TAHUN 2022 - Dion Aulia Putra; Putri Ariscasari; Wardiati Wardiati (Jurnal Real Riset, 2022)
This study aims to find out what factors influence hearing loss in workers at the PT Delima Makmur Palm Oil Mill factory, North Singkil District, Aceh Singkil Regency in 2022." This research is descriptive analytical research with cross sectional approach. The population in this study were all palm oil factory workers at PT Delima Makmur, North Singkil District in 2022, amounting to 98 people. The sample in this study is the total population. Data were collected using a questionnaire and then analyzed using simple linear regression. The results of the study showed that the results of a simple linear regression test showed that there was an effect of working period p = 0.001 with hearing loss and no effect of working age p = 0.213, no effect of length of exposure per day p = 0.225, and no effect of using APT p = 0.392 with hearing loss in oil palm factory workers PT Delima Makmur North Singkil District, Aceh Singkil Regency in 2022. This means that one variable has an influence and four variables have no effect on hearing loss in oil palm factory workers PT Delima Makmur North Singkil District Aceh Singkil Regency 2022.Keywords: Hearing Loss, Age, Working Period, Use of APT.